Evaluation of in vitro and in vivo anticancer activities of potassium koetjapate: a solubility improved formulation of koetjapic acid against human colon cancer - Seyedeh Fatemeh Jafari; Maryam Keshavarzi; Amin MalikShah AbdulMajid; Fouad Saleih R Al-Suede; Muhammad Asif; Mohamed B Khadeer Ahamed; Md Shamsuddin Sultan Khan; Loiy Ahmed Elsir Hassan; Aman Shah Abdul Majid; Mohsen Naseri (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: The previous work on koetjapic acid (KA) isolated from Sandoricum koetjape showed its efficacy towards colorectal cancer however KA has poor water solubility which poses the biggest hindrance to its efficacy. In the present paper, an attempt was made to study the anti-colon cancer efficacy of KA's potassium salt i.e. potassium koetjapate (KKA) applying in vitro and in vivo methods. Experimental approach: KKA was produced by a semi-synthetic method. A human apoptosis proteome profiler array was applied to determine the protein targets responsible for the stimulation of apoptosis. Three doses of KKA were studied in athymic nude mice models to examine the in vivo anti-tumorigenic ability of KKA. Findings/Results: The results of this study demonstrated that KKA regulates the activities of various proteins. It downregulates the expression of several antiapoptotic proteins and negative regulators of apoptosis including HSP60, HSP90, Bcl-2, and IGF-1 in HCT 116 cells with consequent upregulation of TRAILR-1 and TRAILR-2, p27, CD40, caspase 3, and caspase 8 proteins. Additionally, KKA showed an in vitro antimetastatic effect against HCT 116 cells. These results are feasibly related to the down-regulation of Notch, Wnt, hypoxia, and MAPK/JNK and MAPK/ERK signalling pathways in HCT 116 cells besides the up-regulation of a transcription factor for cell cycle (pRb-E2F) pathways. In addition, KKA revealed potent inhibition of tumor growth. Conclusion and implications: In sum, the findings indicate that KKA can be a promising candidate as a chemotherapeutic agent against colorectal cancer.